Pacemaker implantation via femoral vein and successful arrhythmia management in an elderly patient with Fontan circulation: a case report. Issue 1 (13th January 2022) - Mizuno, Tomofumi; Nishii, Nobuhiro; Morita, Hiroshi; Ito, Hiroshi
Abstract: Background: The frequency of arrhythmias increases after the Fontan operation over time; atrial tachycardia (AT) and sinus node dysfunction (SND) are frequently observed. Case summary: Our patient was 63-year-old woman who underwent a lateral tunnel Fontan operation for double outlet right ventricle at age 36. She experienced paroxysmal AT for 1 year, and antiarrhythmic medication was not feasible due to symptomatic SND. Computed tomography revealed a 45 mm-sized thrombus in the high right atrium (RA). The patient had three coexisting conditions: paroxysmal AT, symptomatic SND, and the right atrial thrombus, for which total cavopulmonary connection conversion and epicardial pacemaker implantation (PMI) would have been effective; however, given her age and comorbidities, surgical treatment was considered high risk. Catheter ablation was avoided because of the right atrial thrombus. Finally, a transvenous pacemaker was implanted via the right femoral vein to avoid the right atrial thrombus and severe venous tortuosity from the left subclavian vein to the RA. After PMI, the patient was prescribed amiodarone and bisoprolol for AT suppression. Atrial tachycardia occurred once in the third month after discharge. We increased the dose of amiodarone, and she has been tachycardia-free. Discussion: Transvenous PMI must be considered in cases where open thoracic surgery or catheter ablation cannot be performed. This is the first report of transvenous PMI via the right femoral vein and successful AT and SND management in an elderly Fontan patient.